2022
DOI: 10.1136/bmjopen-2022-061758
|View full text |Cite
|
Sign up to set email alerts
|

Impact of meibomian gland dysfunction on quality of life and mental health in a clinical sample in Ghana: a cross-sectional study

Abstract: ObjectivesThis study aimed to determine the impact of meibomian gland dysfunction (MGD) on quality of life and psychosomatic conditions.DesignThis was a clinic-based cross-sectional study.SettingThis study was conducted at the eye clinic of the University of Cape Coast, Ghana.Participants215 clinical subjects visiting the clinic for a comprehensive eye examination.Primary and secondary outcome measuresSymptomatic MGD, asymptomatic MGD, quality of life scores, depression, anxiety and stress.Results215 clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…In the absence of an MGD-specific and validated PRO instrument, clinical studies that have assessed patient-reported health outcomes in MGD have generally employed DED-specific instruments, such as the Ocular Surface Disease Index, 17–24 the Standard Patient Evaluation of Eye Dryness (SPEED), 24–32 the Ocular Comfort Index, 17 the Canadian Dry Eye Assessment, 33 the Symptom Assessment in Dry Eye, 21 , 24 and the Dry Eye-Related Quality-of-Life Score (DEQS) 19 questionnaires, which allow assessment of a range of symptoms associated with ocular discomfort. However, given that many of these symptoms are common to both MGD and DED, the available DED-specific questionnaires are unlikely to be able to differentiate between the 2 conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the absence of an MGD-specific and validated PRO instrument, clinical studies that have assessed patient-reported health outcomes in MGD have generally employed DED-specific instruments, such as the Ocular Surface Disease Index, 17–24 the Standard Patient Evaluation of Eye Dryness (SPEED), 24–32 the Ocular Comfort Index, 17 the Canadian Dry Eye Assessment, 33 the Symptom Assessment in Dry Eye, 21 , 24 and the Dry Eye-Related Quality-of-Life Score (DEQS) 19 questionnaires, which allow assessment of a range of symptoms associated with ocular discomfort. However, given that many of these symptoms are common to both MGD and DED, the available DED-specific questionnaires are unlikely to be able to differentiate between the 2 conditions.…”
Section: Discussionmentioning
confidence: 99%
“… 38 Subsequent evaluation of DEQS in patients with MGD found no significant differences in DEQS scores between those with and without MGD, which may reflect the fact that this PRO instrument was not specifically developed for use in MGD patients. 19 …”
Section: Discussionmentioning
confidence: 99%
“…Assessing and diagnosing a disease process that is felt, not seen (not apparent on typical ocular surface workup), can improve a patient's quality of life and mental health, mitigating the challenges of everyday living (Asiedu et al., 2018; Asiedu, Dzasimatu, et al., 2022). To arrive at a diagnosis of corneal neuropathic pain requires some key features to be present.…”
Section: Clinical Diagnosis Of Neuropathic Painmentioning
confidence: 99%
“…8 The ocular symptoms caused by MGD substantially affect life quality as well as reduce medication adherence, leading to less effectiveness of antiglaucoma treatments, thus increasing the likelihood of blindness. 2,7,9 Therefore, it is crucial to explore an effective and sustainable treatment for glaucoma patients with MGD.…”
Section: Introductionmentioning
confidence: 99%